Burnout Syndrome Among Hemodialysis and Peritoneal Dialysis Nurses (Iranian Journal of Kidney Diseases, 2016)
Introduction. Burnout, a syndrome with 3 dimensions of emotional exhaustion, depersonalization, and reduction of personal accomplishment, is very common among hemodialysis nurses, while data are scarce regarding the prevalence of burnout syndrome (BS) among peritoneal dialysis (PD) nurses. This study aimed to assess and compare demographic and professional characteristics and burnout levels in hemodialysis and PD nurses, and to investigate factors that increase the level of burnout in dialysis nurses. Materials and Methods. A total of 171 nurses from 44 dialysis centers in Turkey were included in a cross-sectional survey study. Data were collected using a questionnaire defining the social and demographic characteristics and working conditions of the nurses as well as the Maslach Burnout Inventory for assessment of burnout level. Results. There was no significant difference in the level of burnout between the hemodialysis and PD nurses groups. Emotional exhaustion and depersonalization scores were higher among the shift workers, nurses who had problems in interactions with the other team members, and those who wanted to leave the unit, as well as the nurses who would not attend training programs. In addition, male sex, younger age, limited working experience, more than 50 hours of working per week, and working in dialysis not by choice were associated with higher depersonalization scores. Personal accomplishment score was lower among the younger nurses who had problems in their interactions with the doctors, who would not regularly attend training programs, and who felt being medically inadequate. Conclusions. Improving working conditions and relations among colleagues, and also providing further dialysis education are necessary for minimizing burnout syndrome. Burnout reduction programs should mainly focus on younger professionals.